Copolymer, molded article, injection molded article, and coated electric wire

By using copolymers containing specific monomer unit ratios and functional groups, and using injection molding and extrusion molding methods, the smoothness, uniformity and high-temperature performance problems of injection molding and coated wires in the prior art are solved, and efficient production of molding and coated wires with excellent performance is achieved.

CN116867820BActive Publication Date: 2025-04-18DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280016140.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-01-31
Publication Date
2025-04-18
Estimated Expiration
2042-01-31

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently produce an injection molded body with excellent surface smoothness by injection molding, and form a coating layer with uniform thickness and few defects on the core wire with small diameters. The molded body lacks wear resistance of 90°C, low carbon dioxide permeability, low reagent permeability, rigidity at high temperature and high temperature tensile creep characteristics.

Method used

A copolymer containing tetrafluoroethylene and perfluoro(propyl vinyl ether) units was used, and the PPVE unit content was 4.1% to 4.9%, the melt flow rate of 372°C was 33.0 g/10 minutes to 45.0 g/10 minutes, and the number of functional groups was less than 50 carbon atoms per 106 main chains. The injection molded body and coated wire were prepared by injection molding and extrusion molding.

Benefits of technology

The injection molded body with excellent surface smoothness is efficiently produced by the injection molding method, and a coating layer with uniform thickness and few defects is formed on the core wire with small diameter. It has wear resistance of 90°C, low carbon dioxide permeability, low reagent permeability, rigidity at high temperature, high temperature tensile creep characteristics, and heat deformation resistance after impregnation of the reagent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004404650220000051
    Figure BDA0004404650220000051
  • Figure BDA0004404650220000161
    Figure BDA0004404650220000161
  • Figure BDA0004404650220000181
    Figure BDA0004404650220000181
Patent Text Reader

Abstract

The present invention provides a copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of the perfluoro(propyl vinyl ether) units is 4.1% to 4.9% by mass relative to all monomer units, the melt flow rate at 372°C is 33.0 g / 10 min to 45.0 g / 10 min, and the number of functional groups is 10 6 The number of carbon atoms in the main chain is 50 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copolymer, a molded article, an injection-molded article and a covered electric wire. Background Art

[0002] Patent Document 1 describes a covered electric wire characterized in that it is formed by coating a core wire with a TFE-based copolymer, wherein the TFE-based copolymer has a TFE unit derived from tetrafluoroethylene [TFE] and a PAVE unit derived from perfluoro(alkyl vinyl ether) [PAVE], wherein the PAVE unit accounts for more than 5% by mass and less than 20% by mass of all monomer units, and the number of unstable terminal groups per 1×10 6 The number of carbon atoms is less than 10, and the melting point of the TFE-based copolymer is above 260°C.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-059690 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The object of the present invention is to provide a copolymer, which can obtain an injection-molded body with excellent surface smoothness at high productivity by injection molding, can easily form a thin coating layer with uniform thickness and few defects on a core wire with a small diameter by extrusion molding, and can obtain a molded body with excellent 90°C wear resistance, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics and heat deformation resistance after reagent immersion.

[0008] Means for solving problems

[0009] According to the present invention, a copolymer is provided, which contains tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of the perfluoro(propyl vinyl ether) units is 4.1% to 4.9% by mass relative to all monomer units, the melt flow rate at 372°C is 33.0 g / 10 minutes to 45.0 g / 10 minutes, and the number of functional groups is 10 6 The number of carbon atoms in the main chain is 50 or less.

[0010] The copolymer of the present invention preferably has a melt flow rate at 372° C. of 33.0 g / 10 min to 39.0 g / 10 min.

[0011] Furthermore, according to the present invention, there is provided an injection-molded article comprising the above-mentioned copolymer.

[0012] Furthermore, according to the present invention, there is provided a covered electric wire comprising a covering layer containing the above-mentioned copolymer.

[0013] Furthermore, according to the present invention, there is provided a molded article comprising the above-mentioned copolymer, wherein the above-mentioned molded article is a can or a wire covering.

[0014] Effects of the Invention

[0015] According to the present invention, a copolymer can be provided, which can obtain an injection-molded body with excellent surface smoothness at high productivity by injection molding, can easily form a thin coating layer with uniform thickness and few defects on a core wire with a small diameter by extrusion molding, and can obtain a molded body with excellent 90°C wear resistance, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics and heat deformation resistance after reagent immersion. DETAILED DESCRIPTION

[0016] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0017] The copolymer of the present invention contains tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units.

[0018] The copolymer (PFA) containing tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units has excellent chemical resistance, and even when in contact with chemicals, it is not easy for the metal components to dissolve into the chemicals, so it is used as a forming material for a tank for storing reagents used to manufacture semiconductors and liquid crystals. In such a tank, a high-temperature reagent is sometimes put into it, so the tank is required to have high-temperature rigidity and high-temperature tensile creep properties. In addition, when the reagent is an alkaline aqueous solution such as an aqueous sodium hydroxide solution, the alkali in the aqueous solution reacts with the carbon dioxide in the external air, reducing the purity of the alkaline aqueous solution, so it is necessary to avoid the mixing of carbon dioxide in the external air. However, for the existing PFA described in Patent Document 1, even if a tank showing sufficient chemical resistance can be formed, it is impossible to form a tank with low carbon dioxide permeability, high-temperature rigidity and excellent high-temperature tensile creep properties.

[0019] It was found that by appropriately adjusting the content of PPVE units, melt flow rate (MFR) and number of functional groups of the copolymer containing TFE units and PPVE units, the moldability of the copolymer is improved, and by using such a copolymer, a molded body with excellent high-temperature wear resistance, low carbon dioxide permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics and heat deformation resistance after reagent impregnation can be obtained. Therefore, by using the copolymer of the present invention, a tank can be easily formed by injection molding. Furthermore, by using the copolymer of the present invention, a tank that is not easy to wear even when a high-temperature solid-liquid slurry is stored, has high reactivity, and is not easy to break or deform even when a high-temperature reagent is stored can be formed, and a tank that can maintain the quality of the stored reagent at a high level can be formed.

[0020] Moreover, by using such a copolymer, a thin coating layer with uniform thickness and few defects can be easily formed on a core wire with a small diameter. Furthermore, by using such a copolymer, an injection molded product with excellent surface smoothness can be obtained with high productivity.

[0021] The copolymer of the present invention is a melt-processable fluororesin. Melt-processability means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine.

[0022] The content of the PPVE unit of the copolymer is 4.1% to 4.9% by mass relative to all monomer units. The content of the PPVE unit of the copolymer is preferably 4.2% by mass or more, more preferably 4.3% by mass or more, further preferably 4.4% by mass or more, particularly preferably 4.5% by mass or more, preferably 4.8% by mass or less, and more preferably 4.7% by mass or less. If the content of the PPVE unit of the copolymer is too little, it is difficult to obtain a molded body with excellent heat deformation resistance after reagent impregnation. If the content of the PPVE unit of the copolymer is too much, it is difficult to obtain a molded body with low carbon dioxide permeability, high temperature rigidity and high temperature tensile creep properties.

[0023] The content of the TFE unit of the copolymer is preferably 95.1% to 95.9% by mass relative to all monomer units, more preferably 95.2% by mass or more, further preferably 95.3% by mass or more, more preferably 95.8% by mass or less, further preferably 95.7% by mass or less, further preferably 95.6% by mass or less, and particularly preferably 95.5% by mass or less. If the content of the TFE unit of the copolymer is too much, it is likely to be difficult to obtain a molded body with excellent heat deformation resistance after reagent impregnation. If the content of the TFE unit of the copolymer is too little, it is likely to be difficult to obtain a molded body with low carbon dioxide permeability, high temperature rigidity and high temperature tensile creep characteristics.

[0024] In the present invention, the content of each monomer unit in the copolymer is determined by 19 Determined by F-NMR method.

[0025] The copolymer may also contain monomer units derived from monomers copolymerizable with TFE and PPVE. In this case, the content of the monomer units copolymerizable with TFE and PPVE is preferably 0 to 1.5% by mass, more preferably 0.05% to 0.8% by mass, and further preferably 0.1% to 0.5% by mass relative to all monomer units of the copolymer.

[0026] Examples of monomers copolymerizable with TFE and PPVE include hexafluoropropylene (HFP), CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer from 2 to 10) a vinyl monomer, CF2=CF-ORf 1 (Where Rf 1 Perfluoro(alkyl vinyl ether) [PAVE] (except PPVE) represented by a perfluoroalkyl group having 1 to 8 carbon atoms), and CF2=CF-OCH2-Rf 1 (Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) and the like. Among them, HFP is preferred.

[0027] The copolymer is preferably at least one selected from the group consisting of a copolymer consisting only of a TFE unit and a PPVE unit and a TFE / HFP / PPVE copolymer, and more preferably a copolymer consisting only of a TFE unit and a PPVE unit.

[0028] The melt flow rate (MFR) of the copolymer is 33.0 g / 10 minutes to 45.0 g / 10 minutes. The MFR of the copolymer is preferably 33.4 g / 10 minutes or more, more preferably 34.0 g / 10 minutes or more, further preferably 34.1 g / 10 minutes or more, particularly preferably 35.0 g / 10 minutes or more, preferably 44.9 g / 10 minutes or less, more preferably 42.0 g / 10 minutes or less, further preferably 39.0 g / 10 minutes or less, and particularly preferably 38.0 g / 10 minutes or less. If the MFR of the copolymer is too low, the moldability of the copolymer is poor, and it is difficult to obtain a molded body with low carbon dioxide permeability and excellent rigidity at high temperatures. If the MFR of the copolymer is too high, it is difficult to obtain a molded body with excellent wear resistance at 90°C and heat deformation resistance after reagent immersion. Furthermore, when the MFR is 39.0 g / 10 minutes or less or 38.0 g / 10 minutes or less, the wear resistance is further improved, so it is preferred.

[0029] Furthermore, by making the MFR of the copolymer within the above range, using such a copolymer, an injection molded body with excellent surface smoothness can be obtained with high productivity, and a thin coating layer with uniform thickness and few defects can be easily formed on a core wire with a small diameter. In addition, by making the MFR of the copolymer within the above range, the number of sparks generated by the coating layer obtained by using such a copolymer can be reduced. Furthermore, by using the copolymer of the present invention, a plurality of small injection molded bodies with thin-walled portions can be manufactured simultaneously.

[0030] In the present invention, MFR is a value obtained as the mass (g / 10 minutes) of a polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372° C. and a load of 5 kg per 10 minutes using a melt indexer in accordance with ASTM D1238.

[0031] The MFR can be adjusted by adjusting the type and amount of the polymerization initiator, the type and amount of the chain transfer agent, etc., used when polymerizing the monomers.

[0032] In the present invention, every 10 6 The number of functional groups per main chain carbon atom is 50 or less. 6The number of functional groups of the main chain carbon atoms is preferably 40 or less, more preferably 30 or less, further preferably 20 or less, further preferably 15 or less, particularly preferably 10 or less, and most preferably less than 6. By making the number of functional groups of the copolymer within the above range, a molded body with excellent 90°C wear resistance, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics and heat deformation resistance after reagent impregnation can be obtained. If the number of functional groups is too large, it is difficult to obtain a molded body with excellent low carbon dioxide permeability, low reagent permeability and high temperature tensile creep characteristics. In addition, it is difficult to easily form a thin coating layer with uniform thickness and few defects on a core wire with a small diameter, or it is difficult to reduce the number of sparks generated by the resulting coating layer.

[0033] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.

[0034] The number of functional groups is specifically determined by the following method. First, the copolymer is formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a differential spectrum with a background spectrum of fully fluorinated functional groups without any functional groups is obtained. The number of functional groups in the copolymer relative to each 1×10 6 The number of functional groups N per carbon atom.

[0035] N=I×K / t (A)

[0036] I: Absorbance

[0037] K: Correction coefficient

[0038] t: film thickness (mm)

[0039] For reference, absorption frequencies, molar absorption coefficients, and correction coefficients for some functional groups are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low-molecular model compounds.

[0040] [Table 1]

[0041] Table 1

[0042]

[0043] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm2) lower than the absorption frequencies of -CF2H, -COF, free -COOH, and bound -COOH, -COOCH3, and -CONH2 shown in the table, respectively. -1 ).

[0044] For example, the functional group number of -COF is the absorption frequency 1883 cm due to -CF2COF. -1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF -1 The total number of functional groups found from the absorption peak at .

[0045] The functional groups are functional groups present at the main chain end or side chain end of the copolymer and functional groups present in the main chain or side chain. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH.

[0046] The functional groups are introduced into the copolymers, for example, by chain transfer agents or polymerization initiators used when manufacturing the copolymers. For example, when alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the copolymer. In addition, by polymerizing monomers having functional groups, the functional groups are introduced into the side chain ends of the copolymers.

[0047] By fluorinating the copolymer having such functional groups, a copolymer having the number of functional groups within the above range can be obtained. That is, the copolymer of the present invention is preferably a fluorinated copolymer. The copolymer of the present invention also preferably has a -CF3 terminal group.

[0048] The melting point of the copolymer is preferably 295° C. to 315° C., more preferably 300° C. or higher, further preferably 303° C. or higher, further preferably 310° C. or lower, further preferably 306° C. or lower. By setting the melting point within the above range, a copolymer can be obtained that provides a molded body that is more excellent in 90° C. wear resistance, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent immersion.

[0049] In the present invention, the melting point can be measured using a differential scanning calorimeter [DSC].

[0050] The carbon dioxide permeability coefficient of the copolymer is preferably 1370 cm 3 mm / (m 2·24h·atm) or less. The copolymer of the present invention has excellent low carbon dioxide permeability because the content of the PPVE unit, the melt flow rate (MFR) and the number of functional groups of the copolymer containing TFE units and PPVE units are appropriately adjusted. Therefore, for example, the tank obtained by using the copolymer of the present invention can be suitably used for storing reagents that do not want carbon dioxide to be mixed into the external air.

[0051] In the present invention, the carbon dioxide permeability coefficient can be measured under the conditions of a test temperature of 70° C. and a test humidity of 0% RH. The carbon dioxide permeability coefficient can be specifically measured by the method described in the Examples.

[0052] The methyl ethyl ketone (MEK) permeability of the copolymer is preferably 61.0 mg·cm / m 2 · days or less. The copolymer of the present invention has excellent low MEK permeability due to the proper adjustment of the content of PPVE units, melt flow rate (MFR) and number of functional groups of the copolymer containing TFE units and PPVE units. That is, by using the copolymer of the present invention, a molded body that is not easily permeable to reagents such as MEK can be obtained.

[0053] In the present invention, the MEK permeability can be measured under the conditions of a temperature of 60° C. and a period of 60 days. The MEK permeability can be specifically measured by the method described in the Examples.

[0054] The copolymer of the present invention can be manufactured by polymerization methods such as suspension polymerization, solution polymerization, emulsion polymerization, bulk polymerization, etc. As the polymerization method, emulsion polymerization or suspension polymerization is preferred. In these polymerizations, various conditions such as temperature and pressure, polymerization initiator, and other additives can be appropriately set according to the composition and amount of the copolymer.

[0055] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0056] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, and the following may be cited as representative examples:

[0057] Dialkyl peroxydicarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate and di-2-ethoxyethyl peroxydicarbonate;

[0058] Peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate;

[0059] Dialkyl peroxides such as di-tert-butyl peroxide;

[0060] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.

[0061] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).

[0062] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydro-dodecafluorohexanoyl)peroxide, di(ω-hydro-tetrafluoroheptanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluoropropionyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluorovaleranoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl ... (ω-chloro-decafluorohexanoyl) peroxide, bis(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, bis(dichloropentafluorobutyryl) peroxide, bis(trichlorooctafluorohexanoyl) peroxide, bis(tetrachloroundecanoyl) peroxide, bis(pentachlorotetrafluorodecanoyl) peroxide, bis(undecachlorotriacontafluorodocosanoyl) peroxide, and the like.

[0063] The water-soluble free radical polymerization initiator may be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc., organic peroxides such as disuccinic acid peroxide and diglutaric acid peroxide, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. A reducing agent such as sulfites may be used in combination with the peroxide, and the amount used may be 0.1 to 20 times that of the peroxide.

[0064] In the polymerization, a surfactant, a chain transfer agent, and a solvent may be used, and conventionally known surfactants, chain transfer agents, and solvents may be used.

[0065] As the surfactant, known surfactants can be used, for example, nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, fluorinated anionic surfactants are preferred, and more preferred are fluorinated anionic surfactants that may or may not contain ether-bonded oxygen (i.e., oxygen atoms can be inserted between carbon atoms) and have a linear or branched carbon number of 4 to 20. The amount of surfactant added (relative to polymerization water) is preferably 50 ppm to 5000 ppm.

[0066] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; etc. The amount of the chain transfer agent added may vary depending on the chain transfer constant of the compound used, and is usually used in the range of 0.01% to 20% by mass relative to the polymerization solvent.

[0067] Examples of the solvent include water and a mixed solvent of water and alcohol.

[0068] In suspension polymerization, in addition to water, fluorinated solvents can also be used. Examples of fluorinated solvents include hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl, etc.; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3, etc.; hydrofluoroalkanes such as CF3CFHCFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, CF3CF2CF2CF2CF2CF2CF2H, etc.; CH3OC2F5, C Hydrofluoroethers such as H3OC3F5CF3CF2CH2OCHF2, CF3CHFCF2OCH3, CHF2CF2OCH2F, (CF3)2CHCF2OCH3, CF3CF2CH2OCH2CHF2, CF3CHFCF2OCH2CF3, etc.; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc., perfluoroalkanes, among which perfluoroalkanes are preferred. From the perspective of suspension and economy, the amount of fluorine-based solvent used is preferably 10% to 100% by mass relative to the aqueous medium.

[0069] The polymerization temperature is not particularly limited and may be 0 to 100° C. The polymerization pressure is appropriately determined depending on the type and amount of the solvent used and other polymerization conditions such as vapor pressure and polymerization temperature, and may generally be 0 to 9.8 MPaG.

[0070] In the case of obtaining an aqueous dispersion containing a copolymer by polyreaction, the copolymer contained in the aqueous dispersion can be precipitated, and the copolymer can be washed and dried to recover the copolymer. In addition, in the case of obtaining a copolymer in the form of slurry by polyreaction, the slurry can be taken out from a reaction vessel, and the copolymer can be washed and dried to recover the copolymer. The copolymer can be recovered in the form of a powder by drying.

[0071] The copolymer obtained by polymerization can also be formed into pellets. There is no particular limitation on the molding method for forming the pellets, and a conventionally known method can be used. For example, a method of using a single-screw extruder, a twin-screw extruder, or a tandem extruder to melt-extrude the copolymer, cut it into a predetermined length, and mold it into pellets, etc. can be cited. The extrusion temperature during melt extrusion needs to be changed according to the melt viscosity and the manufacturing method of the copolymer, and is preferably the melting point of the copolymer + 20°C to the melting point of the copolymer + 140°C. There is no particular limitation on the cutting method of the copolymer, and conventionally known methods such as a wire cutting method, a heat cutting method, an underwater cutting method, and a sheet cutting method can be used. The volatile components in the pellets can also be removed by heating the obtained pellets (degassing treatment). The obtained pellets can also be treated by contacting with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.

[0072] The copolymer obtained by polymerization can also be subjected to fluorination treatment. Fluorination treatment can be carried out by contacting the copolymer that has not been fluorinated with a fluorine-containing compound. Through fluorination treatment, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2 and relatively thermally stable functional groups such as -CF2H of the copolymer can be converted into extremely thermally stable -CF3. As a result, the total number (number of functional groups) of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2 and -CF2H of the copolymer can be easily adjusted to the above range.

[0073] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the above-mentioned fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (such as IF5, ClF3), etc. can be cited.

[0074] The fluorine free radical source such as F2 gas can be 100% concentration, but from the aspect of safety, it is preferably mixed with an inert gas and diluted to 5% to 50% by mass for use, and more preferably diluted to 15% to 30% by mass for use. As the above-mentioned inert gas, nitrogen, helium, argon, etc. can be cited, and nitrogen is preferred from the aspect of economy.

[0075] The conditions of the fluorination treatment are not particularly limited, and the copolymer in a molten state may be brought into contact with the fluorine-containing compound, but it may be generally carried out at a temperature below the melting point of the copolymer, preferably at 20°C to 240°C, and more preferably at 100°C to 220°C. The above-mentioned fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the copolymer that has not been fluorinated is brought into contact with fluorine gas (F2 gas).

[0076] The copolymer of the present invention may be mixed with other components as required to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, dehydrofluorination agents, etc.

[0077] As fillers, for example, silicon dioxide, kaolin, clay, organic clay, talc, mica, aluminum oxide, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, glass fibers, etc. can be cited. As conductive agents, carbon black, etc. can be cited. As plasticizers, dioctyl phthalate, pentaerythritol, etc. can be cited. As processing aids, carnauba wax, sulfone compounds, low molecular weight polyethylene, fluorine-based additives, etc. can be cited. As dehydrofluorination agents, organic onium, amidines, etc. can be cited.

[0078] As the other components, other polymers other than the above copolymers may be used. Examples of the other polymers include fluororesins, fluororubbers, and non-fluorinated polymers other than the above copolymers.

[0079] Examples of the method for producing the composition include a method of dry-mixing the copolymer and other components; a method of preliminarily mixing the copolymer and other components with a mixer and then melt-kneading them with a kneader, melt extruder or the like; and the like.

[0080] The copolymer of the present invention or the above-mentioned composition can be used as a processing aid, a molding material, etc., and is preferably used as a molding material. The aqueous dispersion, solution, suspension, and copolymer / solvent system of the copolymer of the present invention can also be utilized, and they can be applied as a coating, or used for encapsulation, impregnation, or film casting. However, the copolymer of the present invention has the above-mentioned characteristics, and is therefore preferably used as the above-mentioned molding material.

[0081] The copolymer of the present invention or the above-mentioned composition may be molded to obtain a molded product.

[0082] The method for molding the above-mentioned copolymer or the above-mentioned composition is not particularly limited, and injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, roto-lining molding, etc. can be cited. As a molding method, among them, extrusion molding, compression molding, injection molding or transfer molding are preferred, and injection molding, extrusion molding or transfer molding are more preferred because molded bodies can be produced with high productivity, and injection molding is further preferred. That is, as a molded body, extrusion molding, compression molding, injection molding or transfer molding are preferably used, and injection molding, extrusion molding or transfer molding are more preferably used because they can be produced with high productivity, and injection molding, extrusion molding or transfer molding are more preferably used, and injection molding is further preferred. By molding the copolymer of the present invention by injection molding, an injection molded body with excellent surface smoothness can be obtained with high productivity.

[0083] Examples of the molded article containing the copolymer of the present invention include nuts, bolts, joints, films, bottles, washers, wire coatings, tubes, hoses, pipes, valves, sheets, seals, gaskets, tanks, rollers, containers, cocks, connectors, filter housings, filter covers, flow meters, pumps, wafer carriers, wafer boxes, and the like.

[0084] The copolymer of the present invention, the composition or the molded article can be used, for example, in the following applications.

[0085] Films for food packaging, lining materials for fluid delivery pipelines used in food manufacturing processes, gaskets, sealing materials, sheets and other fluid delivery components for food manufacturing equipment;

[0086] Chemical plugs, packaging films, lining materials, gaskets, sealing materials, thin plates and other reagent delivery components for fluid delivery pipelines used in chemical manufacturing processes;

[0087] Lining components for the inner surface of reagent tanks and piping in chemical equipment and semiconductor factories;

[0088] O (square) rings / tubes / gaskets, valve core materials, hoses, sealing materials, etc. used in automobile fuel systems and peripheral devices; fuel delivery components such as hoses and sealing materials used in automobile AT devices;

[0089] Flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in car engines and peripheral devices of automobiles; other automobile components such as automobile brake hoses, air conditioning hoses, radiator hoses, wire covering materials, etc.;

[0090] O (square) rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, gaskets, diaphragms, joints and other reagent delivery components for semiconductor manufacturing equipment;

[0091] Coating rollers, hoses, tubes, ink containers and other coating and ink components for coating equipment;

[0092] Food and beverage conveying components such as tubes or hoses for food and beverages, tubes, hoses, belts, gaskets, joints, etc., food packaging materials, and glass cooking equipment;

[0093] Waste liquid transmission components such as pipes and hoses used for waste liquid transmission;

[0094] Components for high-temperature liquid transmission such as pipes and hoses used for high-temperature liquid transmission;

[0095] Steam piping components such as pipes and hoses used for steam piping;

[0096] Pipe corrosion protection tapes such as tapes wrapped around pipes on ship decks, etc.

[0097] Various covering materials such as wire covering materials, optical fiber covering materials, transparent surface covering materials and back-side agents provided on the light incident side surface of photovoltaic elements of solar cells;

[0098] Diaphragms of diaphragm pumps and sliding components such as various sealing gaskets;

[0099] Weather-resistant covers for agricultural films, various roofing materials, sidewalls, etc.;

[0100] Interior materials used in the construction field, non-combustible fireproof safety glass and other glass covering materials;

[0101] Lining materials for laminated steel sheets used in the home appliance field, etc.

[0102] Further examples of the fuel delivery member used in the fuel system of the above-mentioned automobile include fuel hoses, filler hoses, evaporator hoses, etc. The above-mentioned fuel delivery member can also be used as a fuel delivery member for sour gasoline, alcohol fuel, and fuel added with gasoline additives such as methyl tert-butyl ether resistance and amine resistance.

[0103] The chemical plug and packaging film have excellent chemical resistance to acids, etc. In addition, as the reagent conveying member, there can also be mentioned a corrosion-resistant tape wound around the piping of chemical equipment.

[0104] Examples of the molded article include automobile radiator water chambers, reagent tanks, bellows, partitions, rollers, gasoline tanks, waste liquid transport containers, high temperature liquid transport containers, fisheries and fish farming tanks, and the like.

[0105] Examples of the molded bodies include automobile bumpers, door trims, instrument panels, food processing equipment, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, display screens, liquid crystal display screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, integrated bathrooms, ventilation fans, lighting frames, and the like.

[0106] The molded product containing the copolymer of the present invention has excellent 90°C wear resistance, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics and heat deformation resistance after reagent immersion, and can therefore be suitably used in nuts, bolts, joints, gaskets, valves, plugs, connectors, filter housings, filter covers, flow meters, pumps, etc.

[0107] The molded body containing the copolymer of the present invention can be manufactured at an extremely high injection speed by injection molding, and has excellent wear resistance at 90°C, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation, so it can be suitable for use as a compressed member such as a gasket or a sealing gasket. The gasket or sealing gasket of the present invention can be manufactured at low cost by injection molding, and has excellent wear resistance at 90°C, low carbon dioxide permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation. The compressed member of the present invention has excellent low carbon dioxide permeability, so it can be suitable as a piping member for circulating a reagent such as carbon dioxide that is not desired to be mixed into the external air.

[0108] The size and shape of the compressed member of the present invention can be appropriately set according to the purpose, and there is no particular limitation. The shape of the compressed member of the present invention can be, for example, annular. In addition, the compressed member of the present invention can have a circular, elliptical, quadrilateral with rounded corners, etc. shape when viewed from above, and has a through hole in its central portion.

[0109] The compressed member of the present invention is preferably used as a member for constituting a non-aqueous electrolyte battery. The compressed member of the present invention is particularly suitable as a member used in a state of contact with a non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention may have a liquid contact surface with the non-aqueous electrolyte in the non-aqueous electrolyte battery.

[0110] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery having a nonaqueous electrolyte, and examples thereof include lithium ion secondary batteries, lithium ion capacitors, etc. In addition, members constituting the nonaqueous electrolyte battery include sealing members, insulating members, and the like.

[0111] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. can be used. The non-aqueous electrolyte battery can further include an electrolyte. The electrolyte is not particularly limited, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc. can be used.

[0112] The compressed member of the present invention can be preferably used as a sealing member such as a sealing gasket or a sealing pad, and an insulating member such as an insulating gasket or an insulating sealing pad. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used for electrical insulation. The compressed member of the present invention can also be a member used for both sealing and insulation purposes.

[0113] The compressed member of the present invention has excellent insulating properties because it contains the copolymer. Therefore, when the compressed member of the present invention is used as an insulating member, it can be firmly adhered to two or more conductive members and prevent short circuits for a long time.

[0114] By using the extrusion molding method to mold the copolymer of the present invention, even when the diameter of the core wire is small, the coating will not be disconnected, and a coating layer can be thinly formed on a core wire with a small diameter at a high traction speed, and a coating layer with excellent electrical properties can be formed, so the copolymer of the present invention can be suitable for use as a material for forming a wire coating. Therefore, the coated wire with a coating layer containing the copolymer of the present invention has almost no defects such as spark generation even when the diameter of the core wire is small and the coating layer is thin, and the electrical properties are also excellent. In addition, even when the coated wire of the present invention is used in a humid carbon dioxide gas environment called a sweet environment, the communication performance is not easy to deteriorate, and high reliability can be maintained for a long time.

[0115] The covered electric wire comprises a core wire and a covering layer disposed around the core wire and containing the copolymer of the present invention. For example, an extruded body formed by melt-extruding the copolymer of the present invention on the core wire can be used as the covering layer. The covered electric wire is suitable for LAN cables (Eathernet Cable), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is suitable for transmission cables such as LAN cables (Eathernet Cable) and high-frequency transmission cables.

[0116] As the material of the core wire, for example, a metal conductor material such as copper or aluminum can be used. The core wire preferably has a diameter of 0.02 mm to 3 mm. The core wire diameter is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire diameter is more preferably 2 mm or less.

[0117] As specific examples of the core wire, AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 μm), AWG-26 (solid copper wire with a diameter of 404 μm), AWG-24 (solid copper wire with a diameter of 510 μm), AWG-22 (solid copper wire with a diameter of 635 μm), etc. can be used.

[0118] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm, and the thickness of the coating layer is also preferably 2.0 mm or less.

[0119] As a high-frequency transmission cable, a coaxial cable can be cited. A coaxial cable generally has a structure in which an inner conductor, an insulating coating, an outer conductor layer and a protective coating are sequentially stacked from the core to the periphery. A molded body containing the copolymer of the present invention can be suitably used as an insulating coating containing a copolymer. The thickness of each layer in the above structure is not particularly limited. Generally, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating coating is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective coating is about 0.5 mm to 2 mm.

[0120] The coating layer may contain air bubbles, and the air bubbles are preferably uniformly distributed in the coating layer.

[0121] The average bubble diameter of the bubbles is not limited, and is, for example, preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and particularly preferably 23 μm or less. In addition, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by obtaining an electron microscope image of a cross section of the wire, calculating the diameter of each bubble by image processing, and averaging them.

[0122] The foaming rate of the coating layer may be 20% or more. More preferably, it is 30% or more, further preferably, it is 33% or more, and further preferably, it is 35% or more. The upper limit is not particularly limited, and is, for example, 80%. The upper limit of the foaming rate may also be 60%. The foaming rate is a value calculated as ((specific gravity of the wire coating material - specific gravity of the coating layer) / specific gravity of the wire coating material) × 100. The foaming rate can be appropriately adjusted according to the application by, for example, adjusting the amount of gas inserted in the extruder described later, or by selecting the type of dissolved gas.

[0123] The covered electric wire may also have other layers between the core wire and the covering layer, and may further have other layers (outer layers) around the covering layer. When the covering layer contains bubbles, the electric wire of the present invention may also be a two-layer structure (skin-foam body) in which a non-foam layer is inserted between the core wire and the covering layer; a two-layer structure (foam body-skin body) in which the outer layer is covered with a non-foam layer; and a three-layer structure (skin-foam body-skin body) in which the outer layer of the skin-foam body is covered with a non-foam layer. The non-foam layer is not particularly limited, and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], polyvinyl chloride [PVC] and other resins.

[0124] The covered electric wire can be produced, for example, by heating a copolymer using an extruder and extruding the copolymer onto a core wire in a molten state to form a covering layer.

[0125] When forming the coating, it is also possible to heat the copolymer and, under the state where the copolymer is molten, introduce gas into the copolymer to form the above-mentioned coating containing bubbles. As the gas, for example, a mixture of gases such as chlorodifluoromethane, nitrogen, carbon dioxide or the like or the above-mentioned gases can be used. The gas can be introduced into the heated copolymer in the form of pressurized gas, or it can be produced by mixing a chemical foaming agent in the copolymer. The gas dissolves in the copolymer in a molten state.

[0126] Furthermore, the copolymer of the present invention can be suitably used as a material for products for high-frequency signal transmission.

[0127] The high-frequency signal transmission product is not particularly limited as long as it is a product used for the transmission of high-frequency signals, and examples thereof include (1) insulating plates of high-frequency circuits, insulating materials of connecting components, molded plates such as printed wiring boards, (2) molded bodies such as bases and antenna covers of high-frequency vacuum tubes, and (3) coated wires such as coaxial cables and LAN cables. The high-frequency signal transmission product can be suitably used in equipment that utilizes microwaves, particularly 3 GHz to 30 GHz microwaves, such as satellite communication equipment and mobile phone base stations.

[0128] In the above-mentioned products for high-frequency signal transmission, the copolymer of the present invention can be suitably used as an insulator because of its low dielectric loss tangent.

[0129] As the above-mentioned (1) molded plate, a printed wiring board is preferred from the aspect of obtaining good electrical characteristics. The above-mentioned printed wiring board is not particularly limited, and examples thereof include printed wiring boards of electronic circuits such as mobile phones, various computers, and communication equipment. As the above-mentioned (2) molded body, a radome is preferred from the aspect of low dielectric loss.

[0130] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0131] Example

[0132] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the examples.

[0133] Each numerical value in the examples was measured by the following method.

[0134] (Content of monomer units)

[0135] The content of each monomer unit is measured by an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker BioSpin).

[0136] (Melt Flow Rate (MFR))

[0137] The mass (g / 10 min) of the polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm was determined at 372° C. and a load of 5 kg using a melt indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D1238.

[0138] (Number of functional groups)

[0139] The pellets of the copolymer were formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.3 mm. The film was scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (Spectrum One, manufactured by PerkinElmer)] to obtain an infrared absorption spectrum, and a differential spectrum with a background spectrum of complete fluorination without functional groups was obtained. The absorption peak of a specific functional group in the sample relative to each 1×10 6 The number of functional groups N per carbon atom.

[0140] N=I×K / t(A)

[0141] I: Absorbance

[0142] K: Correction coefficient

[0143] t: film thickness (mm)

[0144] For reference, regarding the functional groups in the present invention, the absorption frequency, molar absorption coefficient and correction coefficient are shown in Table 2. The molar absorption coefficient was determined from the FT-IR measurement data of a low molecular model compound.

[0145] [Table 2]

[0146] Table 2

[0147]

[0148] (Melting Point)

[0149] Using a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Co., Ltd.), the temperature was increased from 200°C to 350°C for the first time at a heating rate of 10°C / min, then cooled from 350°C to 200°C at a cooling rate of 10°C / min, and the temperature was increased from 200°C to 350°C for the second time at a heating rate of 10°C / min. The melting point was determined from the peak of the melting curve generated in the second heating process.

[0150] Comparative Example 1

[0151] 51.8 L of pure water was added to an autoclave with a volume of 174 L. After nitrogen substitution was performed sufficiently, 40.9 kg of perfluorocyclobutane, 2.56 kg of perfluoro(propyl vinyl ether) (PPVE), and 2.29 kg of methanol were added. The temperature in the system was maintained at 35° C. and the stirring speed was maintained at 200 rpm. Then, tetrafluoroethylene (TFE) was pressed into the autoclave to 0.64 MPa, and 0.103 kg of a 50% methanol solution of di-n-propyl peroxydicarbonate was added to start polymerization. Since the pressure in the system decreases as the polymerization proceeds, TFE is continuously supplied to keep the pressure constant, and 0.055 kg of PPVE is added for each 1 kg of TFE supplied. When the additional amount of TFE reaches 40.9 kg, the polymerization is terminated. The unreacted TFE is released, and after the atmospheric pressure in the autoclave is restored, the obtained reaction product is washed with water and dried to obtain 43.1 kg of powder.

[0152] The obtained powder was melt-extruded at 360° C. using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of a TFE / PPVE copolymer. The PPVE content of the obtained pellets was measured by the above-mentioned method.

[0153] The obtained pellets are placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted with N2 gas to 20 volume % is introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the system is temporarily evacuated and F2 gas is introduced again. Furthermore, 0.5 hours later, the system is evacuated again and F2 gas is introduced again. Thereafter, the above-mentioned F2 gas introduction and evacuation operations are continued once within 1 hour, and the reaction is carried out at a temperature of 210°C for 10 hours. After the reaction is completed, the reactor is fully replaced with N2 gas to terminate the fluorination reaction. Various physical properties are measured using the fluorinated pellets by the above-mentioned method.

[0154] Comparative Example 2

[0155] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.24 kg, methanol was changed to 1.91 kg, and PPVE was changed to 0.049 kg additionally added per 1 kg of TFE supplied to obtain 42.9 kg of dry powder.

[0156] Comparative Example 3

[0157] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.85 kg, methanol was changed to 5.87 kg, and PPVE was added by 0.043 kg per 1 kg of TFE supplied to obtain 42.6 kg of dry powder.

[0158] Comparative Example 4

[0159] Unfluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.17 kg, methanol was changed to 3.09 kg, and PPVE was added by 0.048 kg per 1 kg of TFE supplied to obtain 42.9 kg of dry powder.

[0160] Comparative Example 5

[0161] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.66 kg, methanol was changed to 4.03 kg, and PPVE was added by 0.040 kg per 1 kg of TFE supplied to obtain 42.5 kg of dry powder.

[0162] Example 1

[0163] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.98 kg, methanol was changed to 2.82 kg, and PPVE was added by 0.045 kg per 1 kg of TFE supplied to obtain 42.7 kg of dry powder.

[0164] Example 2

[0165] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.11 kg, methanol was changed to 2.76 kg, and PPVE was added by 0.047 kg per 1 kg of TFE supplied to obtain 42.8 kg of dry powder.

[0166] Example 3

[0167] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.24 kg, methanol was changed to 2.64 kg, and PPVE was changed to 0.049 kg additionally added per 1 kg of TFE supplied to obtain 42.8 kg of dry powder.

[0168] Example 4

[0169] The fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.11 kg, methanol was changed to 3.31 kg, 0.047 kg of PPVE was added for every 1 kg of TFE supplied, the heating temperature of the vacuum vibration reactor was changed to 180°C, and the reaction was changed to be carried out at 180°C for 10 hours to obtain 42.8 kg of dry powder.

[0170] The pellets obtained in Examples and Comparative Examples were used to measure various physical properties by the above-mentioned methods.

[0171] [Table 3]

[0172] Table 3

[0173]

[0174] The expression "<6" in Table 3 means that the number of functional groups is less than 6.

[0175] Next, the following properties were evaluated using the obtained pellets. The results are shown in Table 4.

[0176] (Abrasion test)

[0177] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.2 mm was made, and a 10 cm × 10 cm test piece was cut out from it. The test piece was fixed on the test bench of a Taber abrasion tester (No. 101 Special Taber Wear Tester, manufactured by Yasuda Seiki Manufacturing Co., Ltd.), and a wear test was performed using the Taber abrasion tester under the conditions of a test piece surface temperature of 90°C, a load of 500g, a wear wheel CS-10 (grinded with abrasive paper #240 for 20 turns), and a rotation speed of 60rpm. The weight of the test piece was measured after 1000 turns, and the weight of the test piece was further measured after 3000 turns of the test using the same test piece. The amount of wear was calculated using the following formula.

[0178] Wear amount (mg) = M1 - M2

[0179] M1: Test piece weight after 1000 revolutions (mg)

[0180] M2: Test piece weight after 3000 revolutions (mg)

[0181] (Carbon dioxide permeability coefficient)

[0182] Using the pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.1 mm was prepared. The obtained test piece was used to measure the carbon dioxide permeability according to the method described in JIS K7126-1:2006 using a differential pressure gas permeability meter (L100-5000 gas permeability meter, manufactured by Systech illinois). The permeation area was 50.24 cm 2 , the numerical value of the carbon dioxide permeability at a test temperature of 70°C and a test humidity of 0% RH. The carbon dioxide permeability coefficient is calculated by the following formula using the obtained carbon dioxide permeability and the thickness of the test piece.

[0183] Carbon dioxide permeability coefficient (cm 3 mm / (m 2 ·24h·atm))=GTR×d

[0184] GTR: Carbon dioxide permeability (cm 3 / (m 2 24h atm)

[0185] d: Test piece thickness (mm)

[0186] (Methyl ethyl ketone (MEK) permeability)

[0187] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.1 mm was prepared. 2) was added with 10g of MEK, covered with a sheet test piece, and clamped with a PTFE gasket to tighten and seal. The sheet test piece was placed in contact with MEK, kept at a temperature of 60°C for 60 days, then taken out and left at room temperature for 1 hour before measuring the mass loss. The MEK permeability (mg·cm / m 2 ·sky).

[0188] MEK permeability (mg·cm / m 2 ·day) = [mass loss (mg) × thickness of sheet test piece (cm)] / [permeation area (m 2 )·Days (days)]

[0189] (95℃ load deflection)

[0190] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 3 mm was made, from which a test piece of 80×10 mm was cut out and heated at 100°C for 20 hours in an electric furnace. In addition to using the obtained test piece, the test was carried out under the conditions of a test temperature of 30°C to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8MPa, and a flat method using a heat deformation tester (manufactured by Yasuda Seiki Manufacturing Co., Ltd.) according to the method described in JIS K-K7191-1. The load deflection rate was calculated by the following formula. The sheet with a small load deflection rate of 95°C has excellent rigidity at high temperature.

[0191] Load deflection (%) = a2 / a1×100

[0192] a1: Thickness of the test piece before the test (mm)

[0193] a2: Deflection at 95°C (mm)

[0194] (Tensile creep test)

[0195] The tensile creep strain was measured using a Hitachi High-Tech TMA-7100. A sheet with a thickness of about 0.1 mm was made using pellets and a hot press molding machine, and a sample with a width of 2 mm and a length of 22 mm was made from the sheet. The sample was mounted on a measuring fixture with a distance of 10 mm between the fixtures. For the sample, a cross-sectional load of 2.41 N / mm 2 The sample was loaded in a manner of 240°C, and the displacement (mm) of the length of the sample from 90 minutes after the start of the test to 300 minutes after the start of the test was measured, and the ratio of the displacement (mm) of the length to the initial sample length (10 mm) was calculated (tensile creep strain (%)). The sheet with a small tensile creep strain (%) measured at 240°C and 300 minutes is not easy to elongate even when a tensile load is applied in a very high temperature environment, and has excellent high-temperature tensile creep properties.

[0196] (Reagent immersion crack test (heat deformation resistance after reagent immersion))

[0197] Using pellets and a hot press molding machine, a sheet with a thickness of about 2 mm was made. Using a 13.5mm×38mm rectangular dumbbell, the obtained sheet was punched to obtain 3 test pieces. In the center of the long side of each obtained test piece, a 19mm×0.45mm blade was used to cut a notch according to ASTMD1693. Three notched test pieces and 25g of a 30 wt% aqueous solution of NaOH were placed in a 100mL polypropylene bottle, and after heating at 60°C for 720 hours in an electric furnace, the notched test piece was taken out. The three obtained notched test pieces were installed in a stress crack test fixture according to ASTM D1693, and after heating at 60°C for 2 hours in an electric furnace, the notch and its surroundings were visually observed to count the number of cracks. The sheet that does not produce cracks has excellent heat deformation resistance even after being immersed in a reagent.

[0198] ○: The number of cracks is 0

[0199] ×: The number of cracks is 1 or more

[0200] (Surface smoothness)

[0201] The copolymer was injection molded using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., SE50EV-A) at a barrel temperature of 390°C, a mold temperature of 190°C, and an injection speed of 130 mm / s. As a mold, a mold (15 mm×15 mm×0.6 mmt, 4 cavities) in which HPM38 was plated with Cr was used. The surface of the obtained injection molded body was visually observed, and the surface smoothness was evaluated according to the following criteria.

[0202] Advantages: Smooth surface.

[0203] Good: Roughness was observed only on the surface of a portion located near the gate of the mold at 1 / 4 or less.

[0204] Acceptable: Two or four or more rough spots are observed only on the surface of the portion located near the gate of the mold.

[0205] Poor: Roughness was observed over most of the surface.

[0206] (Wire coating characteristics)

[0207] use Using an electric wire coating molding machine (manufactured by TANABE PLASTIC MACHINERY CO., LTD.), coating pellets were extruded with the following coating thickness onto a silver-plated conductor having 19 strands of 0.05 mm thick to obtain a coated electric wire.

[0208] The wire coating extrusion molding conditions are as follows.

[0209] a) Core conductor: conductor diameter is about 0.25mm (0.05mm×19 strands)

[0210] b) Coating thickness: 0.20mm

[0211] c) Diameter of coated wire: 0.65mm

[0212] d) Wire pulling speed: 250m / min)

[0213] e) Extrusion conditions:

[0214] · Single screw extruder with barrel diameter = 30mm, L / D = 24

[0215] Mold (inner diameter) / sheet (outer diameter) = 9.2mm / 4.0mm

[0216] The set temperatures of the extruder were: barrel C-1 (330°C), barrel C-2 (360°C), barrel C-3 (375°C), head H (390°C), die head D-1 (405°C), die head D-2 (395°C). The core wire preheating was set to 80°C.

[0217] (2-1) Whether the covering is disconnected

[0218] The wire coating was continuously molded, and the case where the coating was disconnected once or more within one hour was regarded as uncontinuous molding (×), and the case where the coating was not disconnected was regarded as continuous molding (○).

[0219] (2-2) Number of sparks

[0220] A spark tester (DENSOK HIGH FREQ SPARK TESTER) was installed on the wire coating to evaluate the wire coating defect at a voltage of 1500 V. The molding was continued for 1 hour, and the case of zero spark was regarded as pass (○), and the case of detected spark was regarded as fail (×).

[0221] (2-3) Outer diameter movement range

[0222] The measurement was performed continuously for 1 hour using an outer diameter measuring instrument (ODAC18XY manufactured by Zumbach). The maximum and minimum values ​​were rounded to the third decimal place relative to the target outer diameter of 0.65 mm. The case of ±0.01 mm was recorded as ±0.01, the case of ±0.02 mm was recorded as ±0.02, the case of ±0.03 mm was recorded as ±0.03, and the case where the coating was disconnected was recorded as ×.

[0223] (Dielectric loss tangent)

[0224] The pellets were melt-molded to produce a cylindrical test piece with a diameter of 2 mm. The produced test piece was placed in a 6 GHz cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd. and measured using a network analyzer manufactured by Agilent Technologies. The measurement results were analyzed using the analysis software "CPMA" manufactured by Kanto Electronics Application Development Co., Ltd. on a personal computer connected to the network analyzer, thereby obtaining the dielectric loss tangent (tan δ) at 20°C and 6 GHz.

[0225]

Claims

1. A copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, The content of the perfluoro(propyl vinyl ether) unit is 4.1% to 4.9% by mass based on the total monomer units. The content of tetrafluoroethylene units is 95.1% to 95.9% by mass based on the total monomer units. The melt flow rate at 372°C is 33.0 g / 10 min to 45.0 g / 10 min. The number of functional groups of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is 50 or less.

2. The copolymer according to claim 1, wherein The melt flow rate at 372° C. is 33.0 g / 10 min to 39.0 g / 10 min.

3. An injection molded article comprising the copolymer according to claim 1 or 2. 4 . A covered electric wire comprising a covering layer containing the copolymer according to claim 1 .

5. A molded product comprising the copolymer according to claim 1 or 2, wherein: The molded body is a can or a wire covering.

Citation Information

Patent Citations

  • Covered electric wire, and coaxial cable

    JP2009059690A

  • Covered electric wire and coaxial cable

    CN101364456A

  • Sealing material

    CN103946250A